Changes in Sports Club Participation are Related to Changes in Types of Leisure-Time Physical Activity in Early Adulthood (Baltic Journal of Sport and Health Sciences, 2026)
Adolescent sports club (SC) participants are more physically active compared to non-participants, yet adolescents are known to drop out from SCs with increasing age. Also, leisure-time physical activity (LTPA) is known to decrease with age. However, literature on the longitudinal changes in participation in types of LTPA from age 15 to 23 is scarce, especially related to none, interrupted, or continuous SC participation. This longitudinal cohort study used self-reported data from 383 young adults in the Health Promoting Sports Club study in Finland. Seven patterns of SC participation at age 15, 19, and 23 were created. Changes in types of LTPA in the five patterns, named ‘Never SC participant’, ‘Dropout at age 15’, ‘Dropout at age 19’, ‘Dropout at age 19 but participant at age 23’, and ‘Continuous SC participant’, were analysed by descriptive statistics, McNemar’s, Chi-Square, and Fisher’s tests. A large proportion of the young adults in the patterns ‘Dropout at age 19 but participant at age 23’ and ‘Continuous SC participant’ participated weekly in ball sports (56% and 75%). In all other patterns, the types of LTPA with the highest proportions of weekly participation are endurance type (61%–73%), strength training (44%–60%), and walking (73%–80%). Walking and strength training increased in all patterns from age 15 to 23. In the patterns ‘Dropout at age 15’ or ‘Never SC participant’, the proportions participating weekly in endurance type decreased significantly from age 15 to 23 (81%–>61% and 87%–>70%). A significantly larger proportion of SC participants at age 23 participated weekly in endurance type (76% and 88%) compared to the other patterns at age 23 (61%–73%).To conclude, changes in types of LTPA vary with none, interrupted, or continuous SC participation. Results suggest ball sports are highly associated with SC participation. Participation in endurance type LTPA appears linear, from none to continuous SC participation, suggesting preventing dropout may have positive effects on participation in endurance type LTPA in early adulthood.